STIMULUS TO CATCALLING: A STUDY ON VERBAL SEXUAL HARASSMENT AMONG UNDERGRADUATE STUDENTS (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2023)
This study explains and investigates catcalling among undergraduate students at Udayana University, Denpasar. The stimulus-response theory of George Herbert Mead was applied in a qualitative approach with a descriptive-explanatory design. Men mostly do catcalling. Meanwhile, the sufferers are primarily women. Catcalling stimulates because students are unaware of it; catcalling is frequently portrayed as commonplace in public interactions, and many undergraduates and members of society have no severe responses to verbal sexual harassment, including catcalling. The victim's responses to stimuli are as follows: avoiding; dismissing the perpetrator; trying to ignore any forms of catcalling experienced; expressing discomfort; striking; making eye contact; and reporting to certain other authorities. Catcalling often occurs in the afternoon and evening when people go out for sports and entertainment. The victim prefers to remain silent and avoids the perpetrator at night because of fear. Victims fear that catcalling at night will lead to kidnappings, robberies, and other forms of sexual violence, such as rape. The study indicates that catcalling most often occurs in a quiet place has the potential to trigger other forms of sexual violence.